'Gukurahundi - a moment of madness': memory rhetorics and remembering in the postcolony. Issue 3 (2nd October 2019) - Maedza, Pedzisai
ABSTRACT: Between 1982 and 1987 the Zimbabwean government deployed a North Korean trained military unit, the Fifth Brigade into the Midlands and South Western regions of the country in an operation code-named Gukurahundi (the first flash floods that cleanse the riverbeds of all debris and chaff before the spring rains). By the time the unit's operations were halted, an estimated 20, 000 mostly ethnic Ndebele and Kalanga speaking civilians were dead, with many more displaced, mutilated and traumatised. This paper investigates how the memory of this operation is publicly remembered, commemorated, contested and transmitted through performance. It uses the annual public holiday ' Unity Day ' observed on 22 December and a 2010 artistic exhibition ' Sibathontisele ' (Lets Drip on them) by Owen Maseko as case studies to examine the contrasting and conflicting ways in which the Gukurahundi is memorialised. This account interrogates the ways in which national holidays are used by the state to shape public memory in postcolonial Zimbabwe as a cultural phenomenon and as a contemporary elegy and memorial. This is contrasted with the state's response to counter-memory performances that contest its hegemony over public remembrance.